2021
DOI: 10.37362/jkph.v6i2.591
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Rebusan Daun Kersen Terhadap Kadar Glukosa Darah Penderita Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Bontobahari

Abstract: Diabetes mellitus is one of the biggest health problems in the world. Diabetes mellitus or what is commonly called diabetes (diabetes) is a disease that causes the patient’s body to be unable to control the level of sugar (glycose) in the blood. At this time, many people are doing treatment by using plants as traditional medicine. One of them is cherry leaves. Kersen leaves are believed to reduce blood glucose levels in type II diabetes mellitus sufferers. The purpose of this study was to determine the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on research by Cai et al (2022) found that physical exercise like tai chi can reduce fatigue and stress, so the rate of blood sugar can usually range to 15. This is supported by research by Nusantoro et al (2018), i.e., there is a change level of depression and the rate of glucose in the blood in a sufferer with diabetes mellitus type 2 by applying tai chi 22 . Results study in Indonesia (2021) found the influence of exercise diabetes to decline score depression patient diabetes mellitus with results p<0.00 20 .…”
Section: Nusantoro Ap Et Al/ 2018mentioning
confidence: 81%
“…Based on research by Cai et al (2022) found that physical exercise like tai chi can reduce fatigue and stress, so the rate of blood sugar can usually range to 15. This is supported by research by Nusantoro et al (2018), i.e., there is a change level of depression and the rate of glucose in the blood in a sufferer with diabetes mellitus type 2 by applying tai chi 22 . Results study in Indonesia (2021) found the influence of exercise diabetes to decline score depression patient diabetes mellitus with results p<0.00 20 .…”
Section: Nusantoro Ap Et Al/ 2018mentioning
confidence: 81%